Fully therapeutic laparoscopy for penetrating abdominal trauma in stable patients - Cabrera Vargas, Luis Felipe; Pedraza, Mauricio; Rincon, Francisco Alejandro; Pulido, Jean Andre; Mendoza-Zuchini, Andres; Gomez, Daniel; Moreno-Villamizar, Maria Daniela; Ferrada, Paula; Lopez, Paula; Di Saverio, Salomone (The American journal of surgery, 2022)
The evaluation and management of PAT has evolved in the last 20 years.1 Laparoscopy has become the standard approach for most of the acute care surgery diseases and its utility in trauma has been increasingly investigated.2 In actual reports, surgical exploration in the setting of PAT has been associated with non-therapeutic laparotomy rates of 61%. In their analysis of the National Trauma Bank on abdominal trauma.5 In adults, laparotomy reports a mortality between 11 and 13%; and mean length of hospital stay 6–26 days.6,7 Laparoscopy has decreased the rate of non-therapeutic laparotomies (33.3% morbidity and 5% mortality) in 61%–89%.6,7 In comparison to our study, no mortality cases were reported. The laparoscopic technical skill of the surgeon is crucial for decide whether go from DL to ATL or FTL and conversion to open surgery according to findings, operative visual field, active bleeding, retroperitoneal injury, degree of contamination and general condition of the patient.3 In case of diagnostic doubts and adequate laparoscopic experience, laparoscopy has been shown to be more accurate in detecting intra abdominal injuries in stable patients.2 The rate of ATL or FTL reported in the literature varies between 13,8% and 83%, associated to the surgeons expertise.